Unveiling the Impact of Audience Involvement, Celebrity Worship, Brand Awareness, and Perceived Product Quality on Purchase and Visit Intentions - Siahaan, Juniarty; Sari, Yuca Yolanda; Wijayanti, Cynthia Anna (Research Center and Case Clearing House PPM School of Management, 2024)
The level of popularity of Korean music is in line with the increasing number of K-pop fans in Indonesia. Despite K-Pop's increasing popularity in Indonesia, K-beauty's reputation has declined. This study explores the influence of the Korean wave on consumer behavior in Indonesia, focusing on the K-Pop and K-Beauty industries. The research analyzes the effects of audience involvement, celebrity worship, brand awareness, and perceived product quality on purchase and visit intentions using survey data of 221 K-pop fans. Data were analyzed using Partial Least Squares (PLS). Findings reveal that audience involvement positively influences celebrity worship, which, in turn, boosts brand awareness, and sigficantly impacts perceived product quality. This perceived product quality positively affects consumers' intentions to purchase and visit, highlighting the interconnectedness of these factors. These results underscore the substantial role of audience involvement and celebrity worship in enhancing brand awareness and perceived product quality, which are pivotal in shaping purchase and visit intentions. The study offers valuable insights for businesses and marketers in the K-Pop and K-Beauty industries, emphasizing the need to understand and leverage these dynamics within the Indonesian consumer market.